2019
DOI: 10.1021/acs.estlett.9b00355
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of PFOA and PFOS at the Air–Water Interface

Abstract: Knowledge of perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) accumulation at the air−water interface is critical to understanding the fate and transport of these substances in subsurface environments. The surface tension of aqueous solutions containing PFOA and PFOS at concentrations ranging from 0.1 to >1000 mg/L and with dissolved solids (i.e., cations and anions) commonly found in groundwater was measured using the Wilhelmy plate method. The surface tensions of solutions containing dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
153
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(166 citation statements)
references
References 19 publications
11
153
2
Order By: Relevance
“…The impact of fluid‐fluid interfacial adsorption on PFAS retention and transport in soil was examined initially by Brusseau (), who employed surface tension data for PFAS including two of primary concern—perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS)—and measured air‐water interfacial areas along with a comprehensive retention model to conduct a theoretical assessment. Additional surface‐tension‐based theoretical analyses of PFAS retention have since been reported (Brusseau, , ; Brusseau & Van Glubt, ; Costanza et al, ; Silva et al, ). Miscible‐displacement laboratory experiments demonstrating that adsorption of PFAS at air‐water and NAPL‐water interfaces can be an important retention process in soil and sand materials have also been reported (Brusseau et al, ; Lyu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of fluid‐fluid interfacial adsorption on PFAS retention and transport in soil was examined initially by Brusseau (), who employed surface tension data for PFAS including two of primary concern—perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS)—and measured air‐water interfacial areas along with a comprehensive retention model to conduct a theoretical assessment. Additional surface‐tension‐based theoretical analyses of PFAS retention have since been reported (Brusseau, , ; Brusseau & Van Glubt, ; Costanza et al, ; Silva et al, ). Miscible‐displacement laboratory experiments demonstrating that adsorption of PFAS at air‐water and NAPL‐water interfaces can be an important retention process in soil and sand materials have also been reported (Brusseau et al, ; Lyu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most sources resulted from releases of PFAS at the ground surface, and some of the PFAS has leached through the unsaturated zone to the capillary fringe, and then slowly partitioned to groundwater in the saturated zone. This is why, at some PFAS sites, the concentrations of PFAS in the capillary fringe are much higher than PFAS concentrations in deeper groundwater (Costanza, Arshadi, Abriola, & Pennell, 2019).…”
Section: Qualitative Pfas Analogs From Cvoc and Btex Remediation Expementioning
confidence: 99%
“…The implications of this surfactant behavior are seen in a compartment model developed by Brusseau et al (2019), where the retardation factor for PFOS through unsaturated sand was 7, compared to a retardation factor of 1.8 for completely saturated conditions. Other work has shown that a significant fraction of the PFAS (well over half the total mass in coarse soils) can be retained in the unsaturated zone due to this accumulation at air‐water interfaces (Costanza et al, 2019). Overall the presence of long‐term sustained PFAS source processes increases the need for some type of active remediation (e.g., removal or containment of source materials) but with the realization that not all the source mass can likely be removed at larger PFAS sites.…”
Section: Qualitative Pfas Analogs From Cvoc and Btex Remediation Expementioning
confidence: 99%
“…Three main peaks are present in the C-F vibrational mode region of the IRRAS spectra of PFOA in In response to this apparent deviation from Hofmeister "salting-out" effects, 20,21 to the Szyszkowski equation, 23,24 130…”
Section: Pfoa Adsorption Measurementsmentioning
confidence: 99%